Management of auricular transcutaneous neuromodulation and electro-acupuncture of the vagus nerve for chronic migraine: a systematic review - Fernández-Hernando, David; Fernández-de-las-Peñas, Cesar; Pareja-Grande, Juan A.; García-Esteo, Francisco J.; Mesa-Jiménez, Juan A. (Frontiers in Neuroscience, 2023)
Background Migraine is a type of primary headache that is accompanied by symptoms such as nausea, vomiting, or sensitivity to light and sound. Objective The aim of this study was to conduct a systematic review on the effectiveness of non-invasive neuromodulation, auricular transcutaneous vagus nerve stimulation (at-VNS), and electro-ear acupuncture of the vagus nerve in patients with migraine headaches. Methods Six databases were searched from inception to 15 June 2022 for clinical trials, in which at least one group received any form of non-invasive neuromodulation of the vagus nerve for managing migraine with outcomes collected on pain intensity and related disability. Data, including participants, interventions, blinding strategy, outcomes, and results, were extracted by two reviewers. The methodological quality was assessed with the PEDro scale, ROB, and Oxford scale. Results The search identified 1,117 publications with nine trials eligible for inclusion in the review. The methodological quality scores ranged from 6 to 8 (mean: 7.3, SD: 0.8) points. Low-quality evidence suggests some positive clinical effects for the treatment of chronic migraine with 1 Hz with at-VNS and ear-electro-acupuncture compared with the control group at post-treatment. Some of the studies provided evidence of the relationship between chronic migraine and a possible positive effect as a treatment with at-VNS and the neurophysiological effects using fMRI. Six of the studies provided evidence using fMRI of the relationship between chronic migraine and a possible positive effect as a treatment with at-VNS and the neurophysiological effects. Regarding all included studies, the level of evidence with the Oxford scale was level 1 (11.17%), six studies were graded as level 2 (66.66%), and two studies were graded as level 3 (22.2%). With the PEDro score, five studies got a low methodological score < 5 and only four got a score superior to 5, being highly methodological quality studies. For ROB, most of the studies were high risk and only a few of them received a low risk of bias. The pain intensity, migraine attacks, frequency, and duration were measured by three studies with positive results at post-treatment. And only 7% reported adverse events using at-VNS. All studies reported results at a post-treatment period in their respective main outcomes. And all studies with fMRI provided strong evidence of the relationship between the Locus Coeruleus, Frontal Cortex, and other superior brain areas with the auricular branch of the Vagus nerve with at-VNS. Conclusion Some positive effects regarding the effect of non-invasive neuromodulation, auricular transcutaneous vagus nerve stimulation (at-VNS), and electro-ear acupuncture of the vagus nerve on migraine is reported in the current literature, but there are not enough data to obtain strong conclusions. Systematic review registration This systematic review was registered in the PROSPERO database (registration number: CRD42021265126).